2016
DOI: 10.1002/jctb.5124
|View full text |Cite
|
Sign up to set email alerts
|

Removal of molybdate anions from contaminated waters by brown algae biomass in batch and continuous processes

Abstract: BACKGROUND In recent years, the discharge of heavy metal ions in natural waters has become a serious problem. Among the various techniques that have been employed for heavy metal removal, adsorption is highly effective and economical because low‐cost adsorbents can be employed. Brown algae are a potential biosorbent because of their high uptake capacities for various heavy metal ions. Petalonia fascia biomass immobilized in an agar matrix was tested as a new removal agent of MoVI from contaminated waters. RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For the removal of molybdenum from groundwater, Carnevale et al [129] reported the application of brown seaweed (Petalonia fascia) as an adsorbent. The experiments were performed in batch and continuous systems and results showed that the highest adsorption capacity was 1376 mg/g.…”
Section: Treatment Of Groundwater By Biological Treatment Methodsmentioning
confidence: 99%
“…For the removal of molybdenum from groundwater, Carnevale et al [129] reported the application of brown seaweed (Petalonia fascia) as an adsorbent. The experiments were performed in batch and continuous systems and results showed that the highest adsorption capacity was 1376 mg/g.…”
Section: Treatment Of Groundwater By Biological Treatment Methodsmentioning
confidence: 99%
“…Brown algae are adequate for this purpose, since they show high uptake capacities for various heavy metal ions due to the presence of biopolymers on the algae surface. Petalonia fascia is a brown seaweed that has been considered for Mo +6 removal from contaminated water [133]. The biosorbent prepared by immobilization of the biomass in an agar matrix was tested in batch and continuous sorption experiments.…”
Section: Biological Treatmentsmentioning
confidence: 99%